حكم تحويل الجنس: دراسة تقويمية في ضوء مقاصد الشريعة = The rule of sex change: an evaluative study in light of the Maqāṣid al-Sharī’ah - Hasmady, Farhan; Mat Jubri@Shamsuddin, Mustafa (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
Sex reassignment or sex change is a new and strange phenomenon unknown to our predecessors. Modern medical advances have facilitated the process and technological advances in communication have helped spread this phenomenon among Muslims of today. Muslim scholars rose to the occasion and clarified the legitimate Islamic Fiqh position towards sex reassignment. However, some of those affiliated with Fiqh and Sharī’ah followed a course other than that of the majority credible and authoritative Muslim jurists in the Islamic world. Thus this paper aims to contribute to the correct legal position towards sex reassignment surgery by highlighting the proofs and arguments of the majority of the jurists (Fuqahā), which are based on the Holy Qur’an and Sunnah according to the understanding of the credible authoritative scholars of past and present, and also on the sound logical evidences and the Maqāṣid al-Sharī’ah. This paper only deals with sex reassignment motivated by the inner-sense of belonging to the opposite sex and does not cover sex reassignment done based on other reasons be it valid or invalid.